La Crosse Virus: A Comprehensive Review of Its Emerging Public Health Importance - Feng, Shuo; Feng, Xiuwei; Zhu, Wenbing; Lu, Ke; Niu, Guoyu; Lin, Weiping; Sun, Hengyi (Viral immunology, 2025)
La Crosse virus (LACV), a constituent of the California serogroup (CSG) within the genus in the Peribunyaviridae family, is the causative agent of LACV encephalitis. This form of encephalitis stands as one of the most significant and burgeoning mosquito-borne diseases in the United States, ranking as the second most prevalent mosquito-borne illness following West Nile virus encephalitis. Predominantly identified in the Midwestern, Mid-Atlantic, and Southeastern regions of the United States, LACV primarily afflicts humans through the bites of mosquitoes. Its genome, divided into three segments, encodes proteins that not only facilitate efficient replication within hosts but also hinder host immune responses. Infections by LACV can lead to a spectrum of neurological outcomes, ranging from mild aseptic meningitis to severe encephalitis with the potential for long-lasting neurological deficits. Despite the availability of diagnostic tools, several challenges persist. Currently, the management of LACV infection remains supportive, underscoring the importance of preventative measures in substantially mitigating the infection's incidence and severity. Moreover, global warming elevates the risk of LACV spreading to new territories. This review delves into recent advancements concerning the transmission and pathogenesis of LACV, drawing upon current knowledge regarding its genetic framework, transmission modes, geographical spread, phylogenetic relationships, clinical presentations and neuropathogenic effects, diagnostic approaches, treatment modalities, and prevention strategies.